Taxonomic study of the genus Promalactis Meyrick (Lepidoptera, Oecophoridae) from Hainan Island, China (III) - Hu, Sha; Wang, Shuxia (Zootaxa, 2017)
Seven new species of the genus Promalactis Meyrick, 1908 are described from Hainan Island, China: P. anterodilata sp. nov., P. bitriangula sp. nov., P. longiprocessa sp. nov., P. tenuivalvata sp. nov., P. unifurcata sp. nov., P. apicifurcata sp. nov., and P. longimaculata sp. nov. The female of P. serrata Du, Li & Wang, 2011 is described for the first time. Images of adults and genitalia are provided.